Successful management of pit viper envenoming without antivenom in an intensive care unit (ICU) of a peripheral district hospital of inner terai: a case series - Bijukchhe, Satish; Adhikari, Samikshya; Sanjel, Anup; Banjade, Prakash (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Snakebite is a significant and potentially fatal public health issue worldwide. It can lead to local reactions around the bite site and systemic toxicity. In Nepal, 89 species of snakes are known, of which 17 species are venomous. The country relies on antivenom imported from India. Despite its ineffectiveness against the venom of pit vipers, healthcare providers often administer anti-snake venom to manage pit viper envenomation. Thus, there is a need for a better understanding of local snake species and more effective treatment guidelines for snakebites. Here, we report 20 cases of snakebite with a deranged coagulation profile admitted to the ICU. All patients recovered from envenomation through conservative management without the administration of antivenom. This study aims to identify the clinical presentation and laboratory findings in patients with pit viper envenomation.